1993
DOI: 10.1177/153331759300800302
|View full text |Cite
|
Sign up to set email alerts
|

Experience of at-homeness and homesickness in patients with Alzheimer's disease

Abstract: In order to gain deeper understanding of the patient's everyday life participant and non-participant observations were performed at a groupdwellingforAlzheimerpatients, during one year and eight months. The patients' talking and acting in various situations were noted, and the contexts were described. The phenomena, "longing for home," "on their way home " and "being at home " were identified and regarded as expressions of the experience ofhomesickness and athomeness in the patients.Karin Zingmark, RN, is a Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 13 publications
2
56
0
Order By: Relevance
“…The focus is on the present (Rasmussen et al, 2000; Zingmark et al, 1993; Öhlén, 2000), and even the moment (Rasmussen et al, 2000), with the opportunity to metaphorically transcend time and space (Benzein, 1999; Öhlén, 2000). A person can live a decaying body and have severe illness, but still feel safe by arousing a zest for life (Öhlén et al, 2002) and being aware of their possibilities (Benzein, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The focus is on the present (Rasmussen et al, 2000; Zingmark et al, 1993; Öhlén, 2000), and even the moment (Rasmussen et al, 2000), with the opportunity to metaphorically transcend time and space (Benzein, 1999; Öhlén, 2000). A person can live a decaying body and have severe illness, but still feel safe by arousing a zest for life (Öhlén et al, 2002) and being aware of their possibilities (Benzein, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Normann, Asplund, and Norberg (1998), in a study among formal carers in nursing homes, have shown that episodes of lucidity in people with severe dementia took place when the carers were using person-centered communication and acting close to the patients. Lucidity happens in situations that Zingmark, Norberg, and Sandman (1993) described as follows: "Being one with an important other in a calm atmosphere creates the feeling of being at home" (p. 14). It is possible that the increased attentiveness of the elders experienced by the staff members was a result of the special attention that the staff members and the nurses gave the elders.…”
Section: Figure 1: Comprehensive Understanding Of Quality Aspects Of mentioning
confidence: 98%
“…As the foundation of nursing is the ontological concept of care that consists of a practical, a relational and a moral dimension (Martinsen, 1989), it is naturally desirable that the organization, on a practical level, offers a physical environment that is as homelike as possible (Zingmark et al, 1993), together with the non-under-resourced provision of staff (Duxbury & Whittington, 2005). However, when caring for persons with severe dementia and BPSD, special attention must be paid to the moral dimension.…”
Section: Focus On Organizationmentioning
confidence: 99%
“…Every resident had one or two nurses primarily responsible for his/her daily care. The central principles of philosophy of care were to facilitate daily living by providing for individual needs and social needs, as well as making the experience of care as dignified and homelike as possible (Zingmark et al, 1993).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation